2018
DOI: 10.1088/1674-1056/27/9/097505
|View full text |Cite
|
Sign up to set email alerts
|

Voltage control of ferromagnetic resonance and spin waves

Abstract: The voltage control of magnetism has attracted intensive attention owing to the abundant physical phenomena associated with magnetoelectric coupling. More importantly, the techniques to electrically manipulate spin dynamics, such as magnetic anisotropy and ferromagnetic resonance, are of great significance because of their potential applications in high-density memory devices, microwave signal processors, and magnetic sensors. Recently, voltage control of spin waves has also been demonstrated in several multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The compounds could also be used to detect H 2 S in HeLa cells when cells were pre-treated with NaHS. 52…”
Section: Introductionmentioning
confidence: 99%
“…The compounds could also be used to detect H 2 S in HeLa cells when cells were pre-treated with NaHS. 52…”
Section: Introductionmentioning
confidence: 99%
“…Strain engineering and charge doping are two widely used methods to introduce new phases and effectively tune magnetic properties of the 2D structures. [19][20][21][22][35][36][37][38][39] For instances, on one hand, in strain engineering, Lucas et al have reported the strain-tunable magnetic anisotropy energy (MAE) in 2D SL-CrX 3 (with X = Cl, Br, and I), [36] and on the other hand, charge doping is applied to tune the magnetic properties of SL-CrI 3 . [19] To our knowledge, up to now, the influences of strain and charge doping on the magnetic properties of SL-CrBr 3 have not been discussed in detail in the present literatures.…”
Section: Introductionmentioning
confidence: 99%
“…If the spin precessions are not uniform, the propagation of collective precessions in a ferromagnet forms spin waves (the magnons are the quanta of spin waves). [1,2] The conventional complementary metal-oxidesemiconductor (CMOS) based electronics can no longer meet the requirements of high processing speed, small size, and low power consumption, one of the alternative methods having the ability to satisfy the above requirements is magnonics. [3][4][5][6][7][8][9][10] The aim of magnonics is to use spin waves to transmit, store, and process the information.…”
Section: Introductionmentioning
confidence: 99%